The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.2.22091/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production and characterization of surfactin-like biosurfactant produced by novel strain Bacillus nealsonii S2MT and it's potential for oil contaminated soil remediation

Abstract: Background Biosurfactants, being highly biodegradable, ecofriendly and multifunctional compounds have wide applications in various industrial sectors including environmental bioremediation. Surfactin a member of lipopeptide family which considered as one of the most powerful biosurfactant due to its environmental applications, emulsification activities as well as therapeutic properties. Therefore, the aim of this study to investigate the surfactin like biosurfactants produced by newly strain S2MT and their pot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Our results indicate that Serratia marcescens N2 produces high yield of biosurfactant that increased with the exposure of cell cultures to gamma radiation, the highest yield was obtained at 1000 Gy. This result is higher than that reported by (Phulpoto et al, 2020) who obtained lower yields that were more than half what we obtained even after optimization of cultivation conditions. The use of gamma radiation did not incur any structural changes except in the peptide peak after exposing the cells to 2000 Gy, this change can be attributed to the effect of gamma radiation on the peptide fragment of the biosurfactant (Blanco et al, 2018)reported fragmentation as one of the effects exerted by ionizing radiation on proteins.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Our results indicate that Serratia marcescens N2 produces high yield of biosurfactant that increased with the exposure of cell cultures to gamma radiation, the highest yield was obtained at 1000 Gy. This result is higher than that reported by (Phulpoto et al, 2020) who obtained lower yields that were more than half what we obtained even after optimization of cultivation conditions. The use of gamma radiation did not incur any structural changes except in the peptide peak after exposing the cells to 2000 Gy, this change can be attributed to the effect of gamma radiation on the peptide fragment of the biosurfactant (Blanco et al, 2018)reported fragmentation as one of the effects exerted by ionizing radiation on proteins.…”
Section: Discussioncontrasting
confidence: 89%
“…Although gamma radiation was previously reported by some researchers to induce hyper producing bacterial mutants (El-Housseiny, Aboshanab, Aboulwafa, & Hassouna, 2019)yet in the current study, we used gamma radiation as a tool to enhance biorecovery and decrease the number of steps required for biosurfactant biorecovery. This is considered economic in the bioprocess of biosurfactant production since the steps involves acid precipitation overnight, refrigeration and centrifugation (Phulpoto et al, 2020), the yield obtained is dependent on the amount of biosurfactant released in the cultivation media. Our results indicate that Serratia marcescens N2 produces high yield of biosurfactant that increased with the exposure of cell cultures to gamma radiation, the highest yield was obtained at 1000 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Stability of the biosurfactant at different temperatures makes it useful in food, pharmaceuticals, and cosmetics industries since sterilization at high temperatures and storage at low temperatures are common processes involved in the production(Elazzazy et al 2015). Furthermore, the stability of the biosurfactant at different pH and salinity shows its applicability in soap production, acidic food products, and bioremediation(Prieto et al 2008;Phulpoto et al 2020;Araújo et al 2019).…”
mentioning
confidence: 99%
“…The use of gamma radiation did not incur any structural changes except in the peptide peak after exposing the cells to 2000 Gy, this change can be attributed to the effect of gamma radiation on the peptide fragment of the biosurfactant. Blanco et al [30]reported fragmentation as one of the effects exerted by ionizing radiation on proteins. This result confirms that exposure of cell culture to 1000 Gy can result in yield increase with no structural changes or functional changes.…”
Section: Discussionmentioning
confidence: 99%